2020
DOI: 10.1016/j.jsat.2019.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Outreach to people who survive opioid overdose: Linkage and retention in treatment

Abstract: Cognitive motivation theories contend that individuals have greater readiness for behavioral change during critical periods or life events, and a non-fatal overdose could represent such an event. The objective of this study was to examine if the use of a specialized mobile response team (assertive outreach) could help identify, engage, and retain people who have survived an overdose into a comprehensive treatment program. We developed an intervention, consisting of mobile outreach followed by medication and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 17 publications
1
49
0
Order By: Relevance
“…However, it was observed that patients were experienced with buprenorphine treatment and had high levels of adherence prior to initiating reSET-O, which increases confidence in the value of providing neurobehavioral treatment in addition to buprenorphine treatment. Furthermore, this approach of having each patient act as his or her own control avoids the potential bias involved with comparing to potentially dissimilar populations which may be at a different readiness for change state [38].…”
Section: Discussionmentioning
confidence: 99%
“…However, it was observed that patients were experienced with buprenorphine treatment and had high levels of adherence prior to initiating reSET-O, which increases confidence in the value of providing neurobehavioral treatment in addition to buprenorphine treatment. Furthermore, this approach of having each patient act as his or her own control avoids the potential bias involved with comparing to potentially dissimilar populations which may be at a different readiness for change state [38].…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of other psychological and temperamental factors can also play a role in the opioid epidemic; these include factors such as impulsivity [ 36 ], self-stigma [ 37 ] and self-determination [ 38 ]. Readiness for change is also another factor that is associated with entry into treatment [ 39 ] and the change process during the treatment [ 40 ], although limited data suggest this may not be related to OUD treatment outcome [ 41 ]. Overall, there is an essential need for more research on the role of these and other similar psychosocial factors.…”
Section: Introductionmentioning
confidence: 99%
“…A paramedic and a peer recovery coach are part of an assertive outreach team who locate and engage opioid overdose survivors into treatment. The program is also staffed with a DATA‐waivered nurse practitioner who provides buprenorphine, a licensed chemical dependency counselor who provides substance abuse counseling, and peer recovery coaches who provide support groups and regular check‐ins on participants of the program, and preliminary results suggest that 88% of people are retained in treatment at 30 days 45,46 . Programs such as EPICC (Engaging Patients in Care Coordination) in St. Louis, the RIMO (Recovery Initiation and Management After Overdose) intervention in Chicago, Project POINT (Planned Outreach, Intervention, Naloxone, and Treatment) in Indiana, and AnchorED (Anchor Recovery Center and Emergency Department) in Rhode Island also leverage the lived experience of peer recovery coaches within their programs, because coaches relate to the common challenges and barriers to sustaining treatment 47–50 …”
Section: Resultsmentioning
confidence: 99%